Are histomorphological patterns a predictor for survival in uveal melanoma patients with hepatic metastases undergoing hepatic artery infusion chemotherapy?: Medical imaging : radiation oncology - Steinberg, Hannah Luisa; Ting, Saskia C; Zensen, Sebastian; Ludwig, Johannes Maximilian; Li, Yan; Richly, Heike; Grüneisen, Johannes; Siveke, Jens T; Theysohn, Jens M; Schaarschmidt, Benedikt M (Journal of medical imaging and radiation oncology, 2024)
Introduction In uveal melanoma (UM) patients with hepatic metastases, hepatic artery infusion chemotherapy (HAIC) is a viable, palliative treatment option. To evaluate the impact of two histomorphological patterns (spindle cell vs. epithelioid) of liver metastases on median overall survival (mOS) in UM patients undergoing HAIC. Methods A retrospective analysis with 60 UM patients (29 females, mean age: 61.6 ± 12.1 years) with hepatic metastases was performed. Histomorphological patterns in metastases were analysed and classified as either predominant spindle cell or epithelioid pattern. mOS between both patient groups was analysed using Kaplan-Meier curves and the log-rank test. Results In 73.3% (44/60) of the metastases, a predominant epithelioid pattern, in 21.7% (13/60) a predominant spindle cell pattern, and in 5% (3/60) other patterns were found. No significant differences between patients with an epithelioid (mOS: 14.2 months, 95% CI: 8.8-19.6) and a spindle cell pattern (mOS: 14.4 months, 95% CI: 4.3-24.5) were detected by the log-rank test, χ2(2) = 0.22, P = 0.881. Conclusion Histomorphological patterns of UM metastases do not seem to be a predictor for mOS in UM patients undergoing HAIC.
Erstmals veröffentlicht: 24. September 2024
Gesehen am 27.01.2025